On the identity of some taxa of Coryphiina Zerche, 1990 from Kazakhstan (Coleoptera: Staphylinidae: Omaliinae: Coryphiini) - Shavrin, Alexey V. (Zootaxa, 2021)
Three taxa of the subtribe Coryphiina Zerche, 1990 (Omaliinae: Coryphiini) from south-eastern Kazakhstan are redescribed and illustrated: the genera Murathus Kastcheev, 1999 and M. montanus Kastcheev, 1999, and Coryphiodes tchyldebayevi (Kastcheev, 1999) comb. nov. (ex Coryphium Stephens, 1834).